2009
DOI: 10.1007/bf03326126
|View full text |Cite
|
Sign up to set email alerts
|

Removal of chromium (VI) from aqueous solutions using Lewatit FO36 nano ion exchange resin

Abstract: ABSTRACT:The removal of the chromium (VI) ion from aqueous solutions with the Lewatit FO36 ion-exchange resin is described at different conditions. The effects of adsorbent dose, initial metal concentration, contact time and pH on the removal of chromium (VI) were investigated. The batch ion exchange process was relatively fast and it reached equilibrium after about 90 min of contact. The ion exchange process, which is pH dependent showed maximum removal of chromium (VI) in the pH range 5.0-8.0 for an initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(57 citation statements)
references
References 37 publications
(43 reference statements)
0
52
0
Order By: Relevance
“…The high strength hexamine-containing wastewater is efficiently removed from industrial wastewater by means of a cation exchange resin (Rafati et al 2010;Saadatjou et al 2010). This method requires an expensive cation exchanger resin and remains the trace amounts of hexamine in wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…The high strength hexamine-containing wastewater is efficiently removed from industrial wastewater by means of a cation exchange resin (Rafati et al 2010;Saadatjou et al 2010). This method requires an expensive cation exchanger resin and remains the trace amounts of hexamine in wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…It needs post treatment separation in a slurry system after photocatalyst reaction. Though this can be overcome by converting TiO 2 into nanotubes which resulted in increase surface area and catalytic activity (Fujishima et al, 2006;Khanfekr et al, 2009;Zhu et al, 2009;Rafati et al,2010). Interest in TiO 2 nanotubes photocatalysis increased after the pioneering study of Fujishma and Honda in 1972.…”
Section: Introductionmentioning
confidence: 99%
“…Insoluble anion exchange resins contain anions capable of exchanging with chromium ions in solutions passed over them (Petruzelli et al 1995;Rengaraj et al 2006). Several studies have been reported in the literature to remove chromium from aqueous solutions using ion exchange resins (Cavaco et al 2007;Ibrahim and Jimoh 2008;Rafati et al 2010). Gode and Pehlivan (2003) removed Cr(III) from aqueous streams using Chelax 100 and Lewatit TP 207 cationic exchange resins.…”
Section: Introductionmentioning
confidence: 99%